2015
DOI: 10.1111/jphp.12403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bergamot essential oil and its extractive fractions on SH-SY5Y human neuroblastoma cell growth

Abstract: Our study provides novel insights into the field of the antiproliferative effects of BEO, which could be exploited in the context of a multitarget pharmacological strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 62 publications
(127 reference statements)
0
52
0
Order By: Relevance
“…Similarly, total flavonoids from Citrus paradisi Macfadyen peel, when combined with arsenic trioxide, produced a synergistic effect in reducing the proliferation of leukemia cells and triggering apoptosis [249], suggesting that Citrus extracts could be used as co-adjuvants in cancer therapy. Finally, we have shown that the bergamot essential oil (BEO) obtained by rasping the peel of Citrus bergamia fruits decreased the growth rate of SH-SY5Y neuroblastoma cells [250] by a mechanism correlated to both apoptotic and necrotic cell death [251]. Table 5 summarizes the main characteristics of the above investigations into the anti-cancer properties of Citrus juices and extracts.…”
Section: Anti-cancer Properties Of Citrus Juices and Extractsmentioning
confidence: 99%
“…Similarly, total flavonoids from Citrus paradisi Macfadyen peel, when combined with arsenic trioxide, produced a synergistic effect in reducing the proliferation of leukemia cells and triggering apoptosis [249], suggesting that Citrus extracts could be used as co-adjuvants in cancer therapy. Finally, we have shown that the bergamot essential oil (BEO) obtained by rasping the peel of Citrus bergamia fruits decreased the growth rate of SH-SY5Y neuroblastoma cells [250] by a mechanism correlated to both apoptotic and necrotic cell death [251]. Table 5 summarizes the main characteristics of the above investigations into the anti-cancer properties of Citrus juices and extracts.…”
Section: Anti-cancer Properties Of Citrus Juices and Extractsmentioning
confidence: 99%
“…Amongst CFs, Citrus bergamia Risso et Poiteau (bergamot) has gained an ever‐increasing attention of the scientific community. It found the most appropriate climate conditions in the southern coasts of the Calabria region (Italy), where it is cultivated primarily for the extraction of the essential oil (BEO) from the peel, exploited mainly in cosmetic industry and in aromatherapy (Mannucci et al, ), as well as studied for its activity as antimicrobial (Cirmi, Bisignano, Mandalari, & Navarra, ) and anti‐proliferative agent (Navarra et al, ). Bergamot juice (BJ) has always been considered a by‐product, yet in the last decade, the beneficial effects of its flavonoid‐rich extract (BJe) have been highlighted by several studies (Cirmi et al, ; Ferlazzo, Cirmi, Calapai, et al, ; Mannucci et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that natural product can be used to prevent and/or alleviate several health disorders (2-4), including those affecting the urinary tract (5). Moreover, regular dietary habits coupled with a healthy lifestyle may protect against certain types of cancer (6,7), including PCa. In particular, epidemiological studies have shown that Asiatic populations have lower rates of PCa compared to others races and that Asian men who adopt a lifestyle typical of Western countries because of migration to the United States, have a significantly higher risk of PCa when compared to their native Asian counterparts (8).…”
mentioning
confidence: 99%